Impact of Safety Leadership on Safety Climate in Process Industry Workers: Literature Review - Titus Halomoan Mg; Zulkifli Djunaidi (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Background: Safety climate concerns individual perceptions of safety policies, procedures, practices and behavior in the work environment. The low safety climate increases the risk of work accidents. Improvement safety climate, one of which can be done by increasing safety leadership, which is safety leadership bring policy direction and commitment regarding the importance of occupational safety and health. This research aims to determine the effect safety leadership to safety climate in process industry workers. Method: This research uses the